Math(Please help)

posted by .

Show that (f X g)(x) = (g X f)(x) = x for f(x)= 3x-5 and g(x)= x+5 / 3

I have know idea how to do this.

  • Math(Please help) -

    Isn't
    (3x-5)(x+5)/3 = ((x+5)/3)(3x - 5) ?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. the big idea of energy

    i have to do an assesment about sound. i have to include the big idea of energy. i have no clue what it is! HHEELLPP MMEE!! What do you mean when you say "the big idea of energy"?
  2. math

    Show that the sum of the squares of any five consecutive integers is divisible by 5. I think I should do something with n+(n+1)+(n+2)+(n+3)+(n+4), but I have no idea where to go to from here. Could someone please help me?
  3. Algebra

    If (x+2)² = 25 and x > 0, what is the value of x?
  4. Algebra

    17-Identify the vertex, axis of symmetry and x-intercept(s) of F(x)=(x+5)^2-6. I have no idea how the x intercepts are -5 +/- sq. root 6 and 0. can you show me how this came to be?
  5. English

    Hi for my english class, we have to make an invention using cheap material that is useful, original, and provides a solution to a problem. We actually have to show the class like a prototype of it and I have no idea what to do! Mines …
  6. English

    Hi for my english class, we have to make an invention using cheap material that is useful, original, and provides a solution to a problem. We actually have to show the class like a prototype of it and I have no idea what to do! Mines …
  7. 7th grade math Ms. Sue please help I have no idea!

    #10 On a blueprint, 1 inch = 13 feet. If the dimensions of the playroom on the blueprint are 0.35 inches x 1.25 inches, what are its actual measurements?
  8. INTEGRAL CALCULUS PLEASE HELP!!!

    If F(x)dx=1 from 1 to 25, F(x)dx=4 from 1 to 4, and F(x)dx=9 from 17 to 25, then: 1) What does F(x)dx from 9 to 17=?
  9. math

    F(x)=9x^3+2x^2-5x+4 and g(x)=5x^3-7x+4. What is f(x)-g(x)?
  10. calculus

    Let y = sinx + ztanx,where z is a function of x. If (dy/dx)= z+ cosx, show that (d^2y/dx^2) =-y. I really have no idea how to do this. Please show me

More Similar Questions